Experimental parametric passive solar desalination prototype analysis. (20th November 2021) - Essa, Mohamed A.; Ibrahim, Mostafa M.; Mostafa, Nabil H.
Abstract: Passive solar desalination is a simple system that is convenient for use in arid areas. In this paper, an experimental investigation with a theoretical parametric analysis was performed for a passive solar desalination system composed of an evacuated tube collector integrated with a steel condenser. The impacts of the porosity of the stainless-steel wool in the evaporation section and the radiation shading for the condenser were examined. It was found that the less porosity of the stainless-steel wool achieves an overall efficiency enhancement of 5% compared to the maximum porosity. The condenser's shading achieved an overall efficiency enhancement of 12.4%, compared to the unshaded condenser's case. The theoretical analysis showed that the condensate increases with the increase of both ambient temperature and global solar irradiance, while decreases with the increase of wind speed. The theoretical model was validated with the experimental shading case with maximum error of 8.6% in the overall efficiency. The cost of the produced desalinated water reached 0.01287 $/kg/m 2 in the proposed system. Highlights: Shading of the condenser enhances the condensation and the desalinate rate. The maximum packaging for the stainless-steel wool achieves the best performance. The desalinate rate increases with increasing the ambient temperature. The desalinate rate increases with increasing the solar irradiance. The desalinate rate decreases with the increase in wind speed.